Prevalence of workplace bully in selected public service agency in Malaysia: do destructive leadership behaviour matters? - Omar, Zoharah; Mokhtar, Mazlina; Hamzah, Siti Raba'ah (Universiti Putra Malaysia Press, 2015)
The aim of this study is to describe the prevalence of workplace bully and to determine the influence of destructive leadership behaviour on workplace bullying in a selected public service agency in Malaysia. A total of 112 public service employees’ participated in this study. Data were collected from the respondents using self-administered questionnaire. The findings revealed a high prevalence of workplace bullying (83.2%) in the selected public service agency. The result of the two-step cluster analysis suggested three clusters. The first comprised 43.7% employees which can be categorized as experiencing occasional bullying (M=60.96; SD=9.13), the second cluster comprised 21.8% employees categorized as experiencing regular bullying (M=71.5; SD=19.15), and the final cluster comprised 34.5% employees categorized as experiencing severe bullying (M=81.27; SD=4.23). The most frequent negative acts experienced were being given task with unreasonable or impossible targets or deadlines, being ordered to work below their level of competence and intimidating behaviour. Meanwhile, the least frequent negative acts experienced were being humiliated or ridiculed at work, being shouted at or being the target of spontaneous anger, and practical jokes carried out by people that the employees do not get on with. The findings also showed destructive leadership behaviour has a strong influence on workplace bullying. This study supports the contention that a destructive form of leadership provides fertile ground for workplace bullying.